The Comparative Effectiveness of Conventional and Online Approaches toAcquiring Vocabulary - Sarfaraz Ali; Mehrunisa Jabeen (Spectrum of Engineering Sciences, 2024)
Many people who are learning a second language are interested in determining themost effective or optimal strategy, activity, or method for acquiring vocabulary in that language. This is because the process of learning vocabulary in a second language isdifficult and time-consuming. In spite of the plethora of research that providesrecommendations and conclusions on vocabulary learning, such as the benefits of maintaining a notebook, periodically reviewing vocabulary, and putting vocabularyitems in context, it is still difficult to provide a definitive answer to this question. Thepurpose of this research is to investigate and assess the efficacy of traditional teaching methods that are utilized in upper-intermediate Academic English classes incomparison to the effectiveness of online vocabulary instruction. The students whowere assigned to the control group used flashcards and notebooks to studyvocabulary terms that were taken from ten different reading passages. WordChampwas utilized by the students who were a part of the experimental group in order toconduct an in-depth analysis and study of the particular vocabulary words that wereoffered in the texts. Additionally, both groups were subjected to frequent evaluationsof the language items that were being used. Evaluation of the effectiveness of the twostrategies was carried out with the help of the post-test. Students who were part of the experimental group had a better recollection of the terms they had learned online, according to the findings of a follow-up evaluation that was conducted three monthslater. This was in comparison to the students who were part of the control group.